Harry Potter for Children, Teenagers and Adults - Wyler, Lia (Meta, 2003)
AbstractA professional literary translator recounts her experience in rendering J.K. Rowling’s Harry Potter series into Brazilian Portuguese in regard to working conditions and premises, British cultural marks maintained to preserve foreignness or erased for the sake of fluency and the verisimilitude of a magical world for children between nine and twelve years of age. The purchase and reception of the book, which enjoyed unexpected success, among older teenagers and adults, media coverage, and the unusual visibility attained by the translator, are also briefly discussed.